EX VIVO CORRELATION OF ULTRASONOGRAPHIC SMALL INTESTINAL WALL LAYERING WITH HISTOLOGY IN DOGS. Issue 5 (5th July 2016) - Le Roux, Alexandre B.; Granger, L. Abbigail; Wakamatsu, Nobuko; Kearney, Michael T.; Gaschen, Lorrie
Abstract : Canine ultrasonographic intestinal layers have been reported to correlate with histological layering. However, discrepancies have been reported in people, and additional layers visualized. The aim of this method comparison study was to describe ex vivo canine small intestinal layering and correlate it with histology. Small intestinal samples of 12 adult dogs euthanized for reasons unrelated to gastrointestinal disease were resected immediately following euthanasia, pinned on a Petri dish, and transverse ultrasonographic images acquired in a water bath, using a high‐frequency linear transducer. Transverse histological sections were obtained at the same level. Measurements of the intestinal layers were performed on the ultrasonographic and histological images. No significant statistical differences were noted between the ultrasonographic and histological measurements and strong to very strong ( r > 0.7) positive correlation was observed for all layers, except for the serosa, which had a low moderate positive correlation ( r = 0.479). In addition to the five established layers, a dual mucosal echogenicity was consistently observed, with seven samples presenting an additional inner mucosal severe hyperechogenicity. Histologically, this dual echogenicity was attributed to the intestinal villi (mildly echogenic) and lamina propria (hypoechoic). The additional inner mucosal severe hyperechogenicity observed in seven samples was attributed to mild‐to‐moderate lacteal dilation histologically. In 4/12 ileal samples, an additional hyperechoic mucosal line was also observed parallel to the submucosa, corresponding histologically to prominent Peyer's patches. Finally, a hyperechoic line was observed within the muscularis of all samples, corresponding histologically to the interface between the muscularis longitudinal and circular layers .